Effects of phytase on pig diets digestibilities, bone mineral deposition, performance and manure production - De Faria, Henrique Gonsales [UNESP]; Thomaz, Maria Cristina [UNESP]; Ruiz, Urbano Dos Santos; Robles-Huaynate, Rizal Alcides; Watanabe, Pedro Henrique; De Melo, Gabriel Maurício Peruca; Da Silva, Susana Zaneti [UNESP] (Universidade Estadual de Londrina, 2015)
Two trials were conducted to evaluate phytase addition to diets with corn, rice and soybean meals for swine. In the first trial, the digestibilities of gross energy and crude protein and the availabilities of calcium (Ca) and phosphorous (P) of diets with or without phytase were evaluated in growing barrows (BW 20.42 ± 2.45 kg), using the total feces and feed collection methods. In the second trial, the parameters evaluated were pig performance, mineral contents in the 3rd and 4th metacarpals, feces production and composition of growing and finishing gilts fed one of the following diets: Positive control (PC), formulated to achieve nutrient and energy requirements of growing and finishing gilts; Negative control (NC), diet PC meeting 84% and 65% of Ca and P levels, respectively; Negative control + phytase (PHY), diet NC + 0.01% phytase (500 FTU/kg). Phytase addition improved P and Ca availabilities in 14.34% and 4.08%, respectively, compared with the diet with no phytase, in trial one. In trial two, the deposition of zinc in the metacarpals was improved by the enzyme and Ca, P and copper fecal excretions of the animals from the PC diet were greater than that observed for the PHY animals. Phytase addition improved the use of phytic phosphorous and calcium by the pigs and is recommended as a way to reduce the potential environmental impact of swine production.
Keywords: Calcium; Environmental pollution; Enzyme; Phosphorous; Piglets